Ileo-colic lipomatosis complicated by cecum perforation and mimicking acute appendicitis: a case report. - Cillara, Nicola; Pileri, Giovanni; Mancosu, Gabriella; Lorrai, Paola; Tocco, Maria; Piga, Michela; Sechi, Raffaele (Acta Biomedica Atenei Parmensis, 2022)
Lipomatosis of the colon is rare in clinical practice although the majority of cases are found incidentally. In rare circumstances, patients may presents with acute complications such as bowel obstruction, intussusception, or perforation. Here we report a case of colonic lipomatosis that present as localized peritonitis mimicking acute appendicitis in a young COVID patient. Sixth case in the literature of intestinal perforation peritonitis in intestinal lipomatosis.